Energy Efficiency of Transport and Logistics Infrastructure: The Example of the Republic of Kazakhstan - Sharapiyeva, Madina D.; Duissekul, Kunanbayeva; Gulmira, Nurseiytova; Zhanna, Kozhamkulova (International Journal of Energy Economics and Policy, 2019)
The study investigates existing approaches of assessing energy efficiency of the transport and logistics infrastructure. It also shows the methodology for placing logistics facilities and analyzes the influence of market environment factors on the placement of logistics centers. The paper considers the problem of locating elements of the transport and logistics infrastructure as objects of energy and resource saving of cargo traffic. On the basis of taking into account the identified factors, a method of forming an energy efficient transport and logistics infrastructure is proposed. Keywords: transport and logistics infrastructure, efficiency, energy consumption, logistic approach. JEL Classifications: L91, Q40, R40 DOI: https://doi.org/10.32479/ijeep.8204